CAPS and Munc13: CATCHRs that SNARE Vesicles - James, Declan J. (Frontiers Media S.A., 2013)
CAPS (Calcium-dependent Activator Protein for Secretion, aka CADPS) and Munc13 (Mammalian Unc-13) proteins function to prime vesicles for Ca(2+)-triggered exocytosis in neurons and neuroendocrine cells. CAPS and Munc13 proteins contain conserved C-terminal domains that promote the assembly of SNARE complexes for vesicle priming. Similarities of the C-terminal domains of CAPS/Munc13 proteins with Complex Associated with Tethering Containing Helical Rods domains in multi-subunit tethering complexes (MTCs) have been reported. MTCs coordinate multiple interactions for SNARE complex assembly at constitutive membrane fusion steps. We review aspects of these diverse tethering and priming factors to identify common operating principles.